2005
DOI: 10.1134/1.2010666
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport, penetration depth, and the upper critical magnetic field in ZrB12 and MgB2

Abstract: We report on the synthesis and measurements of the temperature dependence of resistivity, ρ(T ), the penetration depth, λ(T ), and upper critical magnetic field, Hc2(T ), for polycrystalline samples of dodecaboride ZrB12 and diboride MgB2. We conclude that ZrB12 as well as MgB2 behave like simple metals in the normal state with usual Bloch-Grüneisen temperature dependence of resistivity and with rather low resistive Debye temperature, TR = 280 K, for ZrB12 (as compared to MgB2 with TR = 900 K). The ρ(T ) and λ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 45 publications
(89 reference statements)
5
18
1
Order By: Relevance
“…In our recent study of the electron transport and superconducting properties of polycrystalline ZrB 12 [15][16][17][18], we demonstrated that this compound behaves like a normal metal with the usual Bloch-Grüneisen dependence of ρ(T) but with rather low resistive Debye temperature (T R =280 K). The latter is almost three times smaller than Debye temperature obtained from C(T) data [19].…”
Section: Introductionmentioning
confidence: 89%
“…In our recent study of the electron transport and superconducting properties of polycrystalline ZrB 12 [15][16][17][18], we demonstrated that this compound behaves like a normal metal with the usual Bloch-Grüneisen dependence of ρ(T) but with rather low resistive Debye temperature (T R =280 K). The latter is almost three times smaller than Debye temperature obtained from C(T) data [19].…”
Section: Introductionmentioning
confidence: 89%
“…Different conclusions were obtained in the literature by assuming that the Debye temperature has a value between 270 and 300 K and remains constant at least up to 25 K. [13][14][15] The latter assumption is obviously not supported by specific-heat measurements ͑Fig. 4͒; the initial Debye temperature is close to 1000 K and the continuum approximation F͑͒ ϰ 2 does not hold beyond 10 K. At 25 K the deviation with respect to the initial C phonon ͑T͒ ϰ T 3 law is as high as 300%.…”
Section: Resistivity and Electron-phonon Couplingmentioning
confidence: 99%
“…12 However PCS 11 and STS 12 rather indicate very strong coupling with a gap ratio 2⌬͑0͒ / k B T c = 4.8. The symmetry of the superconducting wave function appears to be d wave according to the temperature dependence of the penetration depth, 13 but s wave according to STS and PCS. 11,12 Similar discrepancies appear in the characterization of phonons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations